Gene expression of group II phospholipase A2 in intestine in ulcerative colitis. - Haapamäki, M M (1997)
BACKGROUND: It has been suggested that phospholipase A2 (PLA2) has an essential role in the pathogenesis of inflammatory bowel diseases. AIMS: This study aimed at identifying cells in intestinal and mesenteric tissue samples that might express group II phospholipase A2 (PLA2-II) at the mRNA and enzyme protein levels in patients with ulcerative colitis. PATIENTS AND TISSUE SAMPLES: Tissue samples were obtained from the intestine, mesentery, skeletal muscle, and subcutaneous fat of six patients who underwent panproctocolectomy for severe ulcerative colitis. Mucosal biopsy specimens were obtained from the colon of another group of six patients with ulcerative colitis during routine diagnostic colonoscopies. Tissues from six patients without intestinal inflammatory diseases served as controls. METHODS: Tissue samples were studied by light microscopy, immunohistochemistry for PLA2-II enzyme protein, and in situ hybridisation and northern hybridisation for PLA2-II mRNA. RESULTS: PLA2-II mRNA and PLA2-II protein were detected in metaplastic Paneth cells in six patients and in the columnar epithelial cells of colonic mucosa in four out of six patients with active ulcerative colitis. Positive findings were less numerous in patients with mild ulcerative colitis. Only two out of six control patients had a weak positive signal for PLA2-II mRNA and one of these two patients had a weak positive immunoreaction for PLA2-II in columnar epithelial cells in the colonic mucosa. None of the control patients had metaplastic Paneth cells. CONCLUSIONS: Metaplastic Paneth cells and colonic epithelial cells synthesise PLA2-II in ulcerative colitis. The activity of the PLA2-II synthesis seems to be related to the degree of inflammation in the diseased bowel.